Pengaruh Komposisi Tepung Tapioka dan Daging Serpih Marlin Hitam Terhadap Karakteristik dan Tingkat Kesukaan Fish Nugget - Latif Sahubawa; Siti Ari Budhiyanti; Aprianti Natia Sary (Jurnal Perikanan Universitas Gadjah Mada, 2006)
Fish nugget is a product that made from mixture of minced fish meat, tapioca powder, and condiments. This product can be frozen or saved in cold storage before fried. The objectives of this research were to utilize Black Marlin chunk meat residue in making fish nugget and to know the influences of tapioca powder addition to fish nugget’s characteristics and acceptability. This experiment used Complete Block Randomized Design with six treatments of tapioca powder addition, that consist of a1 (3%), a2 (6%), a3 (9%), a4 (12%), a5 (15%), and a6 (18%), with three repetition as block. Protein content, elasticity, and organoleptic test (color, flavor, taste, and texture) of final product were analyzed. The addition of 3%, 6%, 9%, 12%, 15% and 18% tapioca powder resulting to the reduction of protein content as much as 0%, 4.92%, 10.96%, 11.69%, 13.76% and 15.03%, respectively, and increase the elasticity to 0.51, 0.57, 0.60, 0.68, 0.76 and 0.86 N/mm, respectively. The highest acceptance value of fish nugget color, flavor, taste, and texture were 3.75 (a2), 3.63 (a5), 4.11 (a1), and 3.9 (a5), respectively, whereas the lowest were 3.49 (a6), 3.5 (a6), 3.05 (a6), and 2.98 (a1), respectively. The favorite fish nugget chosen by panelists was a2 treatment nugget with the highest total score of acceptance of 4.00.